Anti-alpha-actinin antibodies are part of the anti-cell membrane antibody spectrum that characterize patients with lupus nephritis (2015)
Anti-membrane autoantibodies (MbA) have been reported in sera from patients with lupus nephritis (LN) but the targets of the MbA remain to be explored, which is the aim of the current study. Sera were collected from 40 patients with LN determined by renal biopsy, and from 30 systemic lupus erythematosus (SLE) patients without clinical evidence of LN. Thirty autoimmune disease control patients (rheumatoid arthritis, Sjogren's syndrome and systemic sclerosis), and 30 healthy controls were also included. Using flow cytometry, the presence of anti-MbA was explored revealing that IgG anti-MbA positivity was associated with LN (62.5% vs 13.3%) when compared to non-LN SLE patients, autoimmune disease patients (6.7%) and healthy controls (0%). Next, using purified plasma membrane fractions from human embryonic kidney (HEK) cells, the more prominent targets and their occurrence rates were located at 50 kDa, 60/65 kDa, 90 kDa, 110 kDa, 180 kDa and 220 kDa. Alpha-actinin (110 kDa) autoAb was characterized as a major target in LN patients positive for anti-MbA, and anti-MbA binding activity was reduced (36.9 +/- 13.7%) in the presence of alpha-actinin. Laminin (200 kDa) was also characterized as a minor target, which was not the case for annexin A2 (36 kDa). Finally, anti-MbA IgG subclass analysis indicated a predominance of IgG2. In conclusion, IgG anti-MbA were detected at high levels in LN patients supporting a primary pathogenic role for anti-MbA and anti-MbA/alpha-actinin+ in LN that needs further research. (C) 2015 Elsevier Ltd. All rights reserved.